Lithium-ion battery separator membranes based on poly(L-lactic acid) biopolymer. (December 2020) - Barbosa, J.C.; Reizabal, A.; Correia, D.M.; Fidalgo-Marijuan, A.; Gonçalves, R.; Silva, M.M.; Lanceros-Mendez, S.; Costa, C.M.
Abstract: Sustainable materials are increasingly needed in lithium ion batteries in order to reduce their environmental impact and improve their recyclability. This work reports on the production of separators using poly (L-lactic acid) (PLLA) for lithium ion battery applications. PLLA separators were obtained by solvent casting technique, by varying polymer concentration in solution between 8 wt% and 12 wt% in order to evaluate their morphology, thermal, electrical and electrochemical properties. It is verified that morphology and porosity can be tuned by varying polymer concentration and that the separators are thermally stable up to 250 °C. The best ionic conductivity of 1.6 mS/cm was obtained for the PLLA separator prepared from 10 wt% polymer concentration in solution, due to the synergistic effect of the morphology and electrolyte uptake. For this membrane, a high discharge capacity value of 93 mAh/g was obtained at the rate of 1C. In this work, it is demonstrated that PLLA is a good candidate for the development of separator membranes, in order to produce greener and environmentally friendly batteries in a circular economy context. Graphical abstract: Image 1 Highlights: Different PLLA membranes have been developed for battery separator applications by varying polymer concentration. The best ionic conductivity of 1.6 mS/cm has been obtained for the PLLA separator membranes. The membranes show excellent properties for environmentally friendly Li-ion battery separators.